Blessed Chavara: A Prophet for the Empowerment of Women - Maria, Jossy (Asian Horizons, 2009)
An important characteristic of our society and of any society is that it is very slow and hesitant in understanding and appreciating the significance of the roles played by its great personalities. A scientist, theologian and mystic, Pere Teilhard de Chardin, was considered almost as a heretic when he was alive during the first half of the twentieth century, especially in the official circles of the Church. But during Vatican II his theological insights were exerting tremendous influence on the theology of the Church so much so that the Pastoral Constitution on the Church in the Modern World has drawn a lot of inspiration and orientation from the teleological and cosmic thinking of this great theologian. Teilhard de Chardin wrote about the world as something sacred. He saw everything in a divine milieu. For him Christ was the Omega point of an evolutionary process moving towards eschatological fulfillment.